Formation of nanoporous Si upon self-organized growth of Al and Si nanostructures. (25th May 2018) - Thøgersen, Annett; Jensen, Ingvild J T; Stange, Marit; Kjeldstad, Torunn; Martinez-Martinez, Diego; Løvvik, Ole Martin; Ulyashin, Alexander G; Diplas, Spyros
Abstract: Nanostructured materials offer unique electronic and optical properties compared to their bulk counterparts. The challenging part of the synthesis is to create a balance between the control of design, size limitations, up-scalability and contamination. In this work we show that self-organized Al nanowires in amorphous Si can be produced at room temperature by magnetron co-sputtering using two individual targets. Nanoporous Si, containing nanotunnels with dimensions within the quantum confinement regime, were then made by selective etching of Al. The material properties, film growth, and composition of the films were investigated for different compositions. In addition, the reflectance of the etched film has been measured.